2022
DOI: 10.3390/biomedicines10071713
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Cerebrospinal Fluid Amyloid and Tau Levels Identifies Mild Cognitive Impairment Patients Progressing to Alzheimer’s Disease

Abstract: Reported levels of amyloid-beta and tau in human cerebrospinal fluid (CSF) were evaluated to discover if these biochemical markers can predict the transition from Mild Cognitive Impairment (MCI) to Alzheimer’s disease (AD). A systematic review of the literature in PubMed and Web of Science (April 2021) was performed by a single researcher to identify studies reporting immunologically-based (xMAP or ELISA) measures of CSF analytes Aβ(1-42) and/or P-tau and/or T-tau in clinical studies with at least two timepoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(335 reference statements)
0
3
0
Order By: Relevance
“…These pathological findings are corroborated by PET imaging studies that associate Tau pathology with cognitive deficits [5], as well as with brain atrophy [6]. CSF-derived biomarkers reflective of misfolded/phosphorylated Tau burden are also associated with the clinically meaningful role of Tau misfolding in the pathogenesis of neurodegeneration [7].…”
Section: Introductionmentioning
confidence: 76%
“…These pathological findings are corroborated by PET imaging studies that associate Tau pathology with cognitive deficits [5], as well as with brain atrophy [6]. CSF-derived biomarkers reflective of misfolded/phosphorylated Tau burden are also associated with the clinically meaningful role of Tau misfolding in the pathogenesis of neurodegeneration [7].…”
Section: Introductionmentioning
confidence: 76%
“…One recent study found no association between several air pollutants and Aβ ratio ( Alemany et al, 2021 ), but others have seen lower concentrations of Aβ1–42 among children living in more polluted areas ( Calderón-Garcidueñas et al, 2018 , 2016 ). Substantial research finds that those with AD have lower concentrations of Aβ1–42 in CSF compared to those with MCI and normal cognition ( Ma et al, 2022 ; Skillbäck et al, 2015 ; Toledo et al, 2015 ). Thus future air pollution studies should stratify by disease stage in order to better evaluate the relation between air pollution and CSF Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a similar impairment in both male and female mice in all forms of spatial learning and memory evaluated, as well as in the exploratory habituation. It is well established that learning and memory deterioration occurs in both AD patients and animal models [ 25 , 60 ]. Notwithstanding, while transgenic models represent genetic forms of AD and require months to develop cognitive impairments, AD is primarily a sporadic disorder [ 61 ].…”
Section: Discussionmentioning
confidence: 99%